2018
DOI: 10.1002/adhm.201701466
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Surface Potential by Controlling the β Phase Content in Poly(vinylidene fluoridetrifluoroethylene) Membranes Enhances Bone Regeneration

Abstract: Bioelectricity plays a vital role in living organisms. Although electrical stimulation is introduced in the field of bone regeneration, the concept of a dose-response relationship between surface potential and osteogenesis is not thoroughly studied. To optimize the osteogenic properties of different surface potentials, a flexible piezoelectric membrane, poly(vinylidene fluoridetrifluoroethylene) [P(VDF-TrFE)], is fabricated by annealing treatment to control its β phases. The surface potential and piezoelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 59 publications
(42 reference statements)
9
74
0
Order By: Relevance
“…This osteoinductive effect may be mainly attributed to the polarization charge derived from the composite membrane surface. The persistent polarization charge generated by the residual polarization of ferroelectric biomaterials could positively promote osteoblast activity, as reported by our previous study28 and other reports 26,27,32,40. These results implied that the polarized BTO/P(VDF-TrFE) nanocomposite membranes had higher osteoinductivity than the PTFE membrane, which might represent a better material for enhancing bone regeneration.
Figure 2Osteogenic differentiation of BM-MSCs on polarized nanocomposite membranes and commercially-available PTFE membranes.
…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This osteoinductive effect may be mainly attributed to the polarization charge derived from the composite membrane surface. The persistent polarization charge generated by the residual polarization of ferroelectric biomaterials could positively promote osteoblast activity, as reported by our previous study28 and other reports 26,27,32,40. These results implied that the polarized BTO/P(VDF-TrFE) nanocomposite membranes had higher osteoinductivity than the PTFE membrane, which might represent a better material for enhancing bone regeneration.
Figure 2Osteogenic differentiation of BM-MSCs on polarized nanocomposite membranes and commercially-available PTFE membranes.
…”
Section: Resultssupporting
confidence: 74%
“…The XRD patterns exhibited typical BTO crystallization characteristics and the ferroelectric β-phase of the P(VDF-TrFE) was detected (Figure 1C), which indicated that the crystalline characteristics of the piezoelectric ceramic BTO and the ferroelectric phase of the polymer P(VDF-TrFE) remained undisturbed during the fabrication process of the nanocomposite membrane. The β-phase in P(VDF-TrFE) has an important role in the piezoelectric and ferroelectric properties of the material31 and exert a positive effect on its biological functions 32Figure 1Characterizations of BTO/P(VDF-TrFE) nanocomposite membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Damaraju et al showed that PVDF scaffolds, which were prepared by electrospinning method and using the voltage of 25 KV, have the highest fraction of β‐phase and the biggest ALP activity and early mineralization for cultured MSCs, in comparison with controls and other voltages. Controlling the β phase content, Zhang et al modulated the surface potential of PVDF‐trifluoroethylene similar to bone tissue and enhanced the osteogenic differentiation of bone marrow mesenchymal stem cells. In an attempt to improve piezoelectric characteristics of the PVDF, Liu et al wrapped it by GO and showed that piezoelectric constant of PVDF/GO nanofibers is 426% higher than pure PVDF fibers.…”
Section: Discussionmentioning
confidence: 99%
“…However, how to control the electrical stimulation to fit the physiological potential is still not clear. Z.C.G., et al (2018) [81] proposed a novel method to control surface potential of the bone membranes for enhancing and optimizing the regenerated bone tissue. Polyvinylidene fluoridetrifluoroethylene (PVDF-TRFE), a flexible and stable bone-healing material, was used as a template to investigate the relationship between osteogenic outcomes and surface potentials, as shown in Figure 8(D).…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%